Efficacy of comprehensive unit-based safety program to prevent ventilator associated-pneumonia for mechanically ventilated patients in China: A propensity-matched analysis - Yi, Xiaomeng; Wei, Xuxia; Zhou, Mi; Ma, Yingying; Zhuo, Jinfeng; Sui, Xin; An, Yuling; Lv, Haijin; Yang, Yang; Yi, Huimin (Frontiers in Public Health, 2022)
Background: Ventilator-associated pneumonia (VAP) is the most common healthcare-associated infection (HAI) in patients with mechanical ventilation. VAP is largely preventable, and a comprehensive unit-based safety program (CUSP) has effectively reduced HAI. In this study, we aim to comprehensively investigate the effect of implementing the CUSP in patients requiring mechanical ventilation. Methods: In this uncontrolled before-and-after trial conducted in two intensive care unit (ICU) settings in China, patients requiring invasive mechanical ventilation were enrolled between January 2016 to March 2022. Propensity score matching (1:1 matching) was used to analyze the effects of CUSP. Univariate and multivariate logistic/linear regression analyses were performed to evaluate the association between the use of CUSP and clinical outcomes. Results: A total of 1004 patients from the transplantation ICU (TICU) and 1001 patients from the surgical ICU (SICU) were enrolled in the study. Before propensity score matching, the incidences of VAP decreased from 35.1/1,000 ventilator days in the no CUSP group to 12.3/1,000 ventilator days in the CUSP group in the TICU setting (adjusted odds ratio [OR], 0.30; 95% confidence interval [CI], 0.15–0.59). The results of the joinpoint regression analysis confirmed that the implementation of CUSP significantly decreased the incidences of VAP. After propensity score matching in TICU setting, the CUSP group reported a lower incidence of VAP (30.4‰ vs. 9.7‰, P = 0.003; adjusted OR = 0.26, 95% CI: 0.10–0.76), lower wound infection ( 3.4% vs. 0.9%, P = 0.048; adjusted OR = 0.73, 95% CI: 0.50–0.95), shorter ICU LOS (3.5(2.3–5.3) d vs. 2.5(2.0–4.5) d; P = 0.003, adjusted estimate = -0.34, 95% CI: -0.92 to -0.14), and higher safety culture score (149.40±11.74 vs. 153.37±9.74; P = 0.002). Similar results were also observed in the SICU setting between the no CUSP and CUSP group. Conclusions: The implementation of CSUP for patients receiving mechanical ventilation could significantly reduce the incidences of VAP, and other infections, prolong the time until the VAP occurrence, reduces the days of antibiotic use for VAP, shorten the ICU and hospital LOS, and enhance the awareness of safety culture.